The Relation among Shared Governance, Empowerment and Job Involvement as Perceived by Medical-Surgical Nursing Staff - Howida H. E. Mahfouz; Shaimaa M. A. Ebraheem; Abeer Y. Mahdy (Evidence-Based Nursing Research)
Background: In recent days, organizations continuously concentrate on applying human resource management practices to improve nursing performance, productivity, quality of care. Therefore, it is essential for nursing staff in health organizations to implement several management practices and techniques such as shared governance, empowerment, and job involvement training, performance appraisal, compensation, career advancement, and team working involvement. Aim: Assess the relation among shared governance, empowerment, and job involvement as perceived by medical-surgical nursing staff. Methods:  A descriptive correlational design used for carrying out this study. The current study was conducted in all units of medical-surgical departments and operating rooms at Benha University Hospitals, Qaliobia Governorate, Egypt. The convenient sample consisted of 250 staff nurses and 100 nursing management staff. Three tools used to collect data, namely; Index Professional Nursing Governance Questionnaire (IPNG), Nursing Staff Empowerment Questionnaire, and Job Involvement Questionnaire. Result: The present study was revealed that the highest mean percent (50.93% & 53%) of nursing staff were related to official authority, while the lowest mean percent (43.91% & 47.33%) of them were related to the ability to set goals and conflict resolution of shared governance. Also, highest mean percent (83.42% & 85.04%) of nursing staff were related to resources and supplies, while the lowest mean percent (82.7% & 80.28%) of nursing management staff and staff nurses were related to support in work and nurses' information respectively. In addition to highest mean percent (79.82% & 81.77%) of nursing staff were related to emotional job involvement, while the lowest mean percent (72.94% & 79.61%) of them were related to behavioral job involvement. Conclusion: The present study concluded that the nursing staff reported a high level of perception regarding shared governance, empowerment, and job involvement. Also, staff nurses had higher mean scores than nursing management staff regarding shared governance model and job involvement, while the nursing management staff had higher mean scores than staff nurses related to all dimensions of nurses' empowerment except resources and supplies. Besides, there was a statistically significant positive correlation among shared governance, nurses' empowerment, and job involvement for nursing staff. Also, it was evident that when shared governance increased this enhances nurses' empowerment, and it will improve job involvement among nursing. The study recommended create a supporting work environment, keeping open lines of communication through periodical staff meeting, seeking for opinion, and treating them with respect also for nursing management staff should be trained about empowerment, and shared governance models that reflected to develop nurses' involvement and skills to help them to be mastering in doing tasks effectively and efficiently. Also, further research study needs to conduct on the effect of an educational training program about shared governance, empowerment, and job involvement on nurses' outcomes, and organizational progress.